Enhancing capacities to eradicate violence against women (UN New YorkUS, 2013)
Captures the significant regional and national knowledge that has been accumulated on measuring violence against women through the interregional project "Enhancing capacities to eradicate violence against women," through networking of local knowledge communities. Aims to make the knowledge, materials and tools produced through the interregional project widely accessible.
Keywords: VIOLENCE AGAINST WOMEN